Farmers and consumers perceptions and preferences for Yellow Flesh Cassava (YFC) in the central region of Ghana - Adu, Emmanuel Ogyiri; Amenorpe, Godwin; Taah, Kingsley Joseph; Asare, Paul Agu; Parkes, Elizabeth; Labuschagne, Maryke; Kulakow, Peter (Science and Education Publishing Co., Ltd., 2023)
Vitamin A deficiency related diseases are a major problem in Sub-Sahara Africa and any staple crop that contains high levels of total carotenoids including β-carotene can be used to combat these challenges. However, there is little or no information on farmers’ and consumers’ perceptions and preferences for yellow flesh cassava varieties that contain high levels of total carotenoids. This study was done to assess the perceptions and preferences of Ghanaian farmers and consumers for yellow flesh cassava varieties. A survey was conducted on cassava farmers and consumers in Abura-Asebu-Kwamankese, Agona East, Asikuma-Odoben-Brakwa, Assin South, and Twifo-Ati-Morkwa, which are the five major cassava-growing districts in the Central region. In all, 600 respondents consisting of 200 farmers and 400 consumers were interviewed using a content validated structured questionnaire. Data were analysed using SPSS version 25 and showed that 91.2% of the consumers and 88.8% of the farmers have heard of the yellow flesh cassava and 72% were willing to cultivate it, but lack of planting materials and non-availability of a ready market were their major constraints. Also, the majority of the farmers and consumers recommended that fufu and gari be made from the yellow flesh cassava. It is recommended that breeders should breed for mealy yellow flesh cassava to meet demand. More sensitization is also needed to increase the patronage for yellow flesh cassava.